Assessment of Bacterial Contamination in Abattoir Effluents from Bangaie and New Market Areas of Bida, Niger State - Ayisa, Timothy Terna; Muhammad, Ramatu Gogo; Mohammed, Jibrin Ndejiko (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Abattoirs are known for the provision of well-processed meat. The large quantities of waste generated often contribute to the pollution of the environment as they are disposed of into the surrounding soils and water. There has been a growing emphasis in the past few decades on the need to maintain water quality and prevent diseases. The study seeks to assess bacterial contamination in abattoir effluent from two major abattoirs located in Bida, Niger state. Abattoir effluent samples were collected from both abattoirs for the isolation and identification of bacteria using conventional scientific methods. The total colony counts (TCC) at the New market abattoir washing points were 4.3x104 for Bacillus subtilis, Bacillus cereus, Klebsiella pneumonia, Lactobacillus bulgaricus, while the TCC was 1.3x104 for Bangaie abattoir butchering point, and the TCC was 3.2x102 for New market abattoir butchering point, and TCC was 1.3x103 for Bangaie abattoir washing point, Bacillus subtilis, Bacillus cereus, Klebsiella pneumonia, Lactobacillus bulgaricus and Micrococcus luteus. The results from the study indicated that the level of contamination was above the standard limits, thus posing a threat to public health if discharged untreated, and this could lead to disease outbreaks. This study provides an insight into the level of contamination by bacteria and the effect of consuming food or water contaminated by these microbes. Given the negative impacts of abattoir effluents on the quality of water, there is a need to practice proper and effective waste management to reduce the level of pollution and safeguard environmental and public health.